Induction of Mitochondrial Alternative Oxidase in Response to a Cell Signal Pathway Down-Regulating the Cytochrome Pathway Prevents Programmed Cell Death - Vanlerberghe, Greg C. (American Society of Plant Physiologists, 2002)
Treatment of tobacco (Nicotiana tabacum L. cv Petit Havana SR1) cells with cysteine (Cys) triggers a signal pathway culminating in a large loss of mitochondrial cytochrome (cyt) pathway capacity. This down-regulation of the cyt path likely requires events outside the mitochondrion and is effectively blocked by cantharidin or endothall, indicating that protein dephosphorylation is one critical process involved. Generation of reactive oxygen species, cytosolic protein synthesis, and Ca(2+) flux from organelles also appear to be involved. Accompanying the loss of cyt path is a large induction of alternative oxidase (AOX) protein and capacity. Induction of AOX allows the cells to maintain high rates of respiration, indicating that the lesion triggered by Cys is in the cyt path downstream of ubiquinone. Consistent with this, transgenic (AS8) cells unable to induce AOX (due to the presence of an antisense transgene) lose all respiratory capacity upon Cys treatment. This initiates in AS8 a programmed cell death pathway, as evidenced by the accumulation of oligonucleosomal fragments of DNA as the culture dies. Alternatively, wild-type cells remain viable and eventually recover their cyt path. Induction of AOX in response to a chemical inhibition of the cyt path (by antimycin A) is also dependent upon protein dephosphorylation and the generation of reactive oxygen species. Common events required for both down-regulation of the cyt path and induction of AOX may represent a mechanism to coordinate the biogenesis of these two electron transport paths. Such coordinate regulation may be necessary, not only to satisfy metabolic demands, but also to modulate the initiation of a programmed cell death pathway responsive to mitochondrial respiratory status.